On the recent negative relationship between Arctic Oscillation and Indian summer monsoon. (December 2022) - Sandhya, M.; Sridharan, S.
Abstract: The relationship between Arctic Oscillation Index (AOI) and southwest monsoon rainfall (SWMR) over India is re-examined by dividing the AOI and SWMR data for the years 1957–2018 into three nearly two-decade segments. The results from the correlation analysis reveal that though the expected positive correlation is observed between February AOI and SWMR during 1957–1977 and 1978–1998, the correlation drastically changes to negative during 1999–2018. It is suggested that the weakening of cross-equatorial flow due to the positive Atlantic sea surface temperature anomaly during 1999–2018 might have contributed to the unusual behaviour. Highlights: Well known positive relation between AOI and SWMR changes to negative. The inverse relation between Atlantic SST and SWMR dominates during 1999-2018.